Analysis Of The Influence Of Website Quality, Pricing, Customer Trust And Brand Image On Purchase Intention Of Marketplace Customers - Frans Sudirjo; Silvia Ekasari; Bahtiar Efendi; Luh Komang Candra Dewi; Muhammad Asir (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
The situation of online market company rivalry, which is occasionally becoming more competitive, is what drives this research. As a result, businesses need to develop new marketing tactics in order to both keep and increase their market share. This study looked at how purchase intention was influenced by factors such as price, website quality, brand image, and trust. A questionnaire was used to gather the data for this investigation. Purposive sampling was utilized to choose the sample, which consisted of 100 online shoppers. Using the SPSS program, multiple linear regression was used to examine the data. The findings demonstrated that the single factor influencing purchase intention is the trust variable. Price, website quality, and brand image all have a partially zero impact on purchase intention. Purchase intention is significantly impacted by the factors of trust, brand image, price, and quality all at the same time. Purchase intention is influenced by trust, brand image, price, and website quality.